Toxicity of fungicides to honey bees (Hymenoptera: Apidae) and their effects on bee foraging behavior, pollen viability and fruit set on blooming apples and pears - Mayer, D. R.; Kovács, G. (International Journal of Horticultural Science, 1999)
Fungicides fosetyl-AL, triadimefon, dodine, mycobutanil and fenarimol were tested for honey bee (Apis mellifera L.) mortality and effect on bee foraging, pollen viability and fruit set in blooming apple and pear. None of the materials were toxic to honey bees or reduced pollen gemination or fruit set.